Implementasi Manajemen Keuangan Yayasan Guna Menghasilkan Pendidikan Yang Bermutu (Yayasan Sayap Ibu Banten) - Hendri Gunawan; Vega Anismadiyah; Vidya Amalia (Universitas Pamulang, 2023)
This Community Service is entitled Implementation of Foundation Financial Management toGet Qualified Education. The activity was carried out at the Yayasan Sayap Ibu Banten fromMay to June 2022. In improving the quality of education, teachers have a very importantposition and strategy in developing the potential of students. Teachers play a big role in theglory and safety of the nation’s future through inculcating noble basic values as the ideals ofnational education by forming a physically and spiritually prosperous personality, which ispursued through religious education and general education. The purpose of carrying outcommunity service activities is to provide counseling, assistance and a question and answerprocess on the importance of implementing Foundation Financial Management to ProduceQualified Education. The method of community service activities consists of three stages ofactivity. The first stage is the preparation stage in conducting a survey of partner locations,activity participants and preparing materials. The second stage is the implementation whichincludes giving lectures on the implementation ofFoundation Financial Management to Produce Quality Education. The third stage isevaluation, among others, to find out how deep the understanding of the training participants tothe material provided. The conclusion of this community service activity is that the Owners,Leaders, Management and Teachers of the Yayasan Sayap Ibu Banten are enthusiastic inaccepting new knowledge and actively asking questions about how to implement theFoundation's Financial Management to Produce Qualified Education.Keywords: Implementation of Financial Management, Qualified Education